Perbedaan Variasi Waktu Kontak Karbon Aktif Biji Plastik terhadap Penurunan Kadar Amonia pada Limbah Cair di PT Harapan Kurnia Textile Indonesia - Bambang Purnama, Lubis; Nabila Nur Athifa; Ujang Nurjaman (Poltekkes Kemenkes Bengkulu, 2025)
Industrial liquid waste is an effluent from industry which has poor quality which can cause contamination of groundwater and surface water. Production liquid waste containing ammonia comes from the dyeing production process. The results of the laboratory examination obtained an ammonia level of 22.92 mg/L, which means that the ammonia level is still abovethe PerMenLHK quality standard No 5 of 2014, which is 8 mg/L. The purpose of this study was to determine the differences in contact time variation of activated carbon adsorbent media with plastic pellets on the reduction of ammonia levels in the liquid waste produced by the production. The research method used in this research was an experiment with a pretest- posttest without control research design.The sample used is the liquid waste produced by PT. Harapan kurnia Textile Indonesia. The One Way Anova test shows that there is a significant difference between contact time variations in reducing ammonia levels because it has a p value < ɑ (0.000 ≥ 0.05) Ho is rejected and Ha is accepted, thus the test results are significant. The most significant reduction in ammonia levels was at 60 minutes contact time with a reduction percentage of 62.56%. In this research, it is necessary to conduct further research regarding the saturation point of activated carbon media in adsorbing ammonia levels and contact time which is more effective in reducing ammonia levels. Future researchers can carry out further research on the saturation point of plastic pellets activated carbon media in adsorbing ammonia levels.